Context-aware wireless sensor networks for assisted living and residential monitoring - Wood, Anthony D.; Stankovic, John A.; Virone, Gilles; Selavo, Leo; He, Zhimin; Cao, Qiuhua; Doan, Thao; Wu, Yafeng; Fang, Lei; Stoleru, Radu (IEEE network, 2008)
Improving the quality of healthcare and the prospects of "aging in place" using wireless sensor technology requires solving difficult problems in scale, energy management, data access, security, and privacy. We present AlarmNet, a novel system for assisted living and residential monitoring that uses a two-way flow of data and analysis between the front- and back-ends to enable context-aware protocols that are tailored to residents' individual patterns of living. AlarmNet integrates environmental, physiological, and activity sensors in a scalable heterogeneous architecture. The SenQ query protocol provides real-time access to data and lightweight in-network processing. Circadian activity rhythm analysis learns resident activity patterns and feeds them back into the network to aid context-aware power management and dynamic privacy policies.